2021
DOI: 10.1002/mrd.23542
|View full text |Cite
|
Sign up to set email alerts
|

Biological roles of l‐carnitine in oocyte and early embryo development

Abstract: Poor oocyte quality is responsible for female infertility. Multiple studies have been carried out to find supplements to enhance oocyte quality and mitigate infertility problems. L-carnitine and its derivatives have diverse roles in developing oocytes and early embryos. This review focuses on the in vitro and in vivo studies that using L-carnitine alone or in combination with other supplements for oocyte quality enhancement. The key roles of L-carnitine in oocyte quality and embryo growth were summarized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 80 publications
0
15
0
1
Order By: Relevance
“…It has been reported that oocytes use lipids as an oxidative substrate for nuclear and/or cytoplasmic maturation [ 40 , 41 , 42 ]. Several studies have revealed that L-carnitine can enhance the competence of oocyte development in mammals [ 43 ]. In contrast, Marin et al (2022) reported that L-carnitine supplementation during maturation culture of buffalo oocytes impaired oocyte development in the presence of fetal bovine serum [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that oocytes use lipids as an oxidative substrate for nuclear and/or cytoplasmic maturation [ 40 , 41 , 42 ]. Several studies have revealed that L-carnitine can enhance the competence of oocyte development in mammals [ 43 ]. In contrast, Marin et al (2022) reported that L-carnitine supplementation during maturation culture of buffalo oocytes impaired oocyte development in the presence of fetal bovine serum [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It acts as an antioxidant by promoting β-oxidation in oocytes, attenuating oxidative damage, and preventing apoptosis. ( Agarwal et al, 2018 ; Li et al, 2021 ) Metabolites in carnitine shuttle metabolism such as acyl-carnitines have also been consistently reported to be affected by traffic-related air pollutants most notably in association with NO 2 . ( van Veldhoven et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a quaternary amine (3-hydroxy-4-N-trimethylaminobutyrate) and exists as two stereoisomers: Lcarnitine (biologically active form) and D-carnitine. L-carnitine is involved in fat metabolism and energy production, especially in skeletal and cardiac muscle cells, as these cells mainly depend on fatty acids as a primary energy source (52). Namely, Lcarnitine carries long-chain fatty acids from the cytosol into the mitochondria to undergo beta-oxidation for ATP production (53).…”
Section: Carnitinementioning
confidence: 99%
“…L-carnitine plays a role in maintaining the cell membrane integrity, in the excretion of intermediate metabolism products, balancing the coenzyme A pool inside the mitochondria, and preventing the accumulation of fatty acids. It also exhibits antioxidant activity by increasing the activity of antioxidant enzymes, improving mitochondrial function, or improving the turnover of membrane phospholipid fatty acids (52,54).…”
Section: Carnitinementioning
confidence: 99%
See 1 more Smart Citation